E-COMMERCE WEBSITE DESIGN USING EXTREME PROGRAMMING METHOD (Case Study: UMKM Bolu Ara) - Juniar, Rina; Nugroho, Imam Ma’ruf; Muhyidin, Yusuf (RISTEC : Research in Information Systems and Technology, 2025)
UMKM Bolu Ara is a micro business engaged in the production of cakes and sponges, which still uses manual methods in recording and managing orders via WhatsApp. This system causes various obstacles such as delays in payment verification, order recording errors, and difficulties in data management. To overcome these problems, the design and development of e-commerce websites using the Extreme Programming (XP) method was carried out. The XP method was chosen because it is iterative and flexible, with stages of planning, design, coding, and testing. The tools used include the CodeIgniter 3 framework, PHP programming language, MySQL database, and Visual Studio Code editor, with XAMPP support as a local server. Testing is done using the Black Box Testing method to ensure system functionality in accordance with user needs. The development results show that the e-commerce website built is able to make the process of recording and managing orders more structured, and provide convenience for users in making transactions independently. This system also supports managers in recording data and reports better.